2001
DOI: 10.1046/j.1365-3024.2001.00388.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of two monoclonal antibodies raised in Btkxid mice that recognize phosphorylcholine‐bearing antigens from Trichinella and other helminths

Abstract: This study investigated the binding properties of two monoclonal antibodies (mAbs US1 and US2) raised in (CBA/n x BALB/c)F1 (NBF1) Btk(xid) male mice. Both mAbs show unusual specificity for phosphorylcholine (PC)-containing TSL4 antigens of Trichinella. Specifically, and in contrast to mAbs raised in normal mice, US1 and US2 mAbs do not bind to artificial PC-protein conjugates and are not inhibited by either free PC or NPPC, although US2 was partially inhibited by NPPC at high concentration (10(-2) M). However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…The low specificity of Trichinella CLE preparations for diagnosis of human trichinellosis has been reported previously (28,44); however, it is believed that CLE preparations may be useful for early detection of Trichinella infections (28,41,44). Although it is expected that some of the antigens contained in CLE preparations may be recognized earlier than TSL-1 antigens, the data presented here suggest that such CLE antigens either are not specific (e.g., phosphorylcholine) (18,40) or have immunogenicity below the threshold of the response induced by immunodominant cross-reactive antigens.…”
Section: Discussionmentioning
confidence: 55%
“…The low specificity of Trichinella CLE preparations for diagnosis of human trichinellosis has been reported previously (28,44); however, it is believed that CLE preparations may be useful for early detection of Trichinella infections (28,41,44). Although it is expected that some of the antigens contained in CLE preparations may be recognized earlier than TSL-1 antigens, the data presented here suggest that such CLE antigens either are not specific (e.g., phosphorylcholine) (18,40) or have immunogenicity below the threshold of the response induced by immunodominant cross-reactive antigens.…”
Section: Discussionmentioning
confidence: 55%
“…Interestingly, the responses to Ascaris glycolipids could be partially inhibited by competition with free PC, but almost completely by HF treatment. This difference might be accounted for by the fact that some antibodies will recognize only the PC moiety and can bind free PC, whereas other antibodies that bind to PC, do so in the context of structures that it is attached to, and therefore will not be competed away by free PC alone (35). The possibility that HF treatment destroys glycolipids was ruled out not only by mass spectrometry, but also functionally by showing intact binding of monoclonal antibodies to LacdiNAc (GalNAc(β1‐4)GlcNAcβ1‐) structures present on glycolipids of Ascaris both before and after treatment with HF (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Based on these observations, we investigated whether HDM allergy development depended on CD36 or PAFR and whether engagement of these receptors on epithelial or dendritic cells in the lung is involved in HDM-induced allergic disease. Induced or passively administered anti-PC IgM antibodies are protective in disease models involving PC-expressing bacteria, parasites, apoptotic cells, and metabolic products (34–39). Similarly, we have shown that increased anti-PC IgM levels in serum and lungs are associated with suppressed allergy development (22).…”
Section: Introductionmentioning
confidence: 99%